2012
DOI: 10.1186/1550-2783-9-29
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory and cardiovascular responses to creatine, glycerol and alpha lipoic acid in trained cyclists

Abstract: BackgroundIt has been shown that supplementation with creatine (Cr) and glycerol (Gly), when combined with glucose (Glu) necessary for the enhancement of Cr uptake by skeletal muscle, induces significant improvements in thermoregulatory and cardiovascular responses during exercise in the heat.PurposeTo determine whether Cr/Gly-induced thermoregulatory and cardiovascular responses are maintained when the majority (~75%) of the Glu in the Cr/Gly supplement is replaced with the insulintropic agent alpha lipoic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…In agreement with Easton et al (2007), BM and TBW increased and while HR and core temperature (T core ) were attenuated, no overall difference were seen in O 2 , RE or in serum osmolarity and plasma volume. Polyviou et al (2012) extended this research and reported that Cr combined with Gly and α-lipoic acid (Ala) had similar effects as the Cr/Gly/glucose combination used by Easton et al (2007) when performing constant load exercise in the heat followed by a 10-mile time trial in a hot humid environment. Despite the fairly consistent effects of Cr-induced hyperhydration (with and without enhancement by other hyperhydrating compounds) on thermoregulatory and cardiovascular responses in the previous studies described, exercise performance in the heat was not enhanced (Kilduff et al 2004;Easton et al 2007;Beis et al 2011;Polyviou et al 2012).…”
Section: Cr Supplementation and Endurance (Aerobic) Exercise Performancementioning
confidence: 66%
See 2 more Smart Citations
“…In agreement with Easton et al (2007), BM and TBW increased and while HR and core temperature (T core ) were attenuated, no overall difference were seen in O 2 , RE or in serum osmolarity and plasma volume. Polyviou et al (2012) extended this research and reported that Cr combined with Gly and α-lipoic acid (Ala) had similar effects as the Cr/Gly/glucose combination used by Easton et al (2007) when performing constant load exercise in the heat followed by a 10-mile time trial in a hot humid environment. Despite the fairly consistent effects of Cr-induced hyperhydration (with and without enhancement by other hyperhydrating compounds) on thermoregulatory and cardiovascular responses in the previous studies described, exercise performance in the heat was not enhanced (Kilduff et al 2004;Easton et al 2007;Beis et al 2011;Polyviou et al 2012).…”
Section: Cr Supplementation and Endurance (Aerobic) Exercise Performancementioning
confidence: 66%
“…No effects on core temperature compared to placebo Reduced plasma volume loss during 1 hour of hyperthermic submaximal exercise Cognitive performance and neuroprotection Jones et al 2009Tan, 2014Haussinger et al 1993 Francaux and Poortmans 1999; Saab et al 2002Kilduff et al 2003Kilduff et al 2004;Easton et al 2007;Beis et al 2011;Polyviou et al 2012Tarnopolsky et al 1997Andrews et al 1998;Hespel et al 2001Fuld et al 2005Easton et al 2009Bennett et al 2001Branch et al 2007 Increase in psychomotor, complex cognitive task and motor skill performance post-sleep deprivation Some evidence of neuroprotection Reduced hypoxic brain damage McMorris et al 2006;McMorris et al 2007;Cook et al 2011Turner et al 2015Carter et al 1995 Footnote: All studies presented in Table 1 are human studies with the exception of Carter et al 1995 and who used in vitro animal models…”
Section: Anaerobic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Enhancement in muscle Cr content facilitates growth in lean body mass, strength, and high intensity exercise performance [ 4 ]. It also enhances fluid retention and provides the improvement in thermoregulation during exercise in the heat [ 5 , 6 ]. As a consequence of these findings, Cr supplementation has become popular amongst recreational and professional athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these possible detrimental changes in plasma lipids induced by high glucose (Glu) intake consumed with Cr containing supplements, there has been a search for alternative agents that stimulate insulin secretion and thus may be expected to enhance skeletal muscle Cr uptake. We previously demonstrated that the same increase in total body water and improvement in thermoregulatory and cardiovascular responses during exercise in the heat can be achieved when part of the Glu in the Cr/glycerol (Gly) hyperhydrating supplement is replaced with alpha lipoic acid (Ala) [ 20 ], a compound that has insulin-potentiating activity [ 21 ]. It remains unclear whether expected changes in plasma lipids can be attenuated by partial replacement of Glu with Ala.…”
Section: Introductionmentioning
confidence: 99%